Characterization and toxicological potential of Alternaria alternata associated with post-harvest fruit rot of Prunus avium in China - Ahmad, Tanvir; Xing, Fuguo; Cao, Changyu; Liu, Yang (Frontiers in Microbiology, 2024)
Post-harvest fruit rot caused by Alternaria species is one of the most important threats to the fruit industry. Post-harvest rot on sweet cherry (Prunus avium) fruit was observed in the fruit markets of the Haidian district of Beijing, China. The fungal isolates obtained from the infected sweet cherry fruits matched the descriptions of Alternaria alternata based on the morphology and multi-gene (ITS, endo-PG, and Alta1) sequence analysis. Pathogenicity tests indicated that ACT-3 was the most virulent isolate, exhibiting typical post-harvest fruit rot symptoms. Physiological studies revealed that the optimal conditions for the growth of ACT-3 were temperature of 28°C, water activity of 0.999, and pH of 8 with 87, 85, and 86 mm radial growth of ACT-3 on a potato dextrose agar (PDA) medium, respectively, at 12 days post-inoculation (dpi). Moreover, the fungus showed the highest growth on a Martin agar medium (MAM) modified (85 mm) and a PDA medium (84 mm) at 12 dpi. The proliferation of the fungus was visualized inside the fruit tissues by confocal and scanning electron microscope (SEM), revealing the invasion and destruction of fruit tissues. Alternaria mycotoxins, tenuazonic acid (TeA), and alternariol (AOH) were detected in five representative isolates by HPLC analysis. The highest concentrations of TeA (313 μg/mL) and AOH (8.9 μg/mL) were observed in ACT-6 and ACT-3 isolates, respectively. This study is the first to present a detailed report on the characteristics and proliferation of A. alternata associated with sweet cherry fruit rot and the detection of toxic metabolites.